2008
DOI: 10.1002/art.23530
|View full text |Cite
|
Sign up to set email alerts
|

Impaired arterial function associated with thinning of cortical bone in rheumatoid arthritis

Abstract: Objective. To evaluate the association between peripheral arterial function and cortical bone thickness in rheumatoid arthritis (RA). Methods. In a cross-sectional study, we measured the combined cortical thickness (CCT) of the second metacarpal bone from hand radiographs, and the ankle-to-arm systolic blood pressure ratio, also known as ankle-brachial index (ABI), in RA patients. We evaluated the association between the 2 using multinomial logistic regression. Results. We obtained CCT and ABI measurements in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Thus, if specialists find bone changes among RA patients, they need to worry about arterial lesions and vice versa. These two findings are separately associated with glucocorticoid use [25].…”
Section: Medication Effectsmentioning
confidence: 81%
See 4 more Smart Citations
“…Thus, if specialists find bone changes among RA patients, they need to worry about arterial lesions and vice versa. These two findings are separately associated with glucocorticoid use [25].…”
Section: Medication Effectsmentioning
confidence: 81%
“…Many studies ruled out smokers from study groups because of the evident vasoconstrictor effect, and only some studies showed a higher prevalence of smokers [5,6]. Not only current smoking but also former smoking harms the vasculature [25]. Inflammatory markers might partially induce higher prevalence of these conditions; tumor necrosis factor-alpha (TNF-alpha), interleukin 10 (IL10), interleukin 6 (IL6), and C-reactive protein (CRP) are correlated with SBP, and CRP, von Willebrand factor (VWF) have a correlation with triglyceride level [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations